The Protestant cause : religious alliance with the West European Calvinist communities as a political issue in England, 1585-1630 - Adams, SL (1973)
It has long been accepted that protestant ideological aspirations played an important role in the foreign policy of England in the period from the Henrican Reformation to the Civil War; but little attempt has been made systematically to analyse the effects of this role. Most discussions of the question have been characterised by a lack of sympathy for protestant aspirations, and have concentrated upon anti-catholicism,relegating the Protestant Cause to the rank of provincial bigotry. This study has been undertaken with the contrary assumption ~ that the Protestant Cause should be seen not merely as a response to catholic threats, but as a positive force which posed the central problem to English foreign policy in this period. Not only did England have the central role to play in the creation of working religious alliances with continental protestant states; but the defence of religion was the leading motive for English intervention on the continent beyond the coastal periphery. The years between Leicester's expedition to the Netherlands in 1585 and England's withdrawal from the Thirty Years War in 1630 mark the period in which the issue had the greatest political effect, for with Leicester's expedition the English monarchy came the closest to undertaking the leadership of the Cause, which it rejected finally upon withdrawal from the Thirty Year’s War.